Use and effectiveness of propolis on chronic periodontitis : a systematic review = Uso y efectividad del propóleo en periodontitis crónica : una revisión sistemática - Fraire Reyes, Irma A.
The aim of this study was to determine the effect of propolis on non-surgical periodontal therapy in patients with chronic periodontitis (CP) as it appears in the recent literature. Propolis is a natural and biocompatible resinous substance that has shown, by means of several scientific studies, to possess medicinal properties such as antimicrobial, healing, anesthetic, anti-inflammatory, and analgesic, among others. There are several studies that have reported the use of propolis as a non-surgical treatment of CP, its comparison with other antimicrobials, and the improvement of clinical and microbiological parameters with scaling and root planing (SRP). A bibliographic search was conducted in the PubMed, Google Scholar, Web of Science, and Science Direct databases up to 2021. The results showed that there are very few reports focused on clinical studies; however, according to the analyzed data, propolis could be a good adjuvant for the treatment of patients with chronic periodontitis compared to the conventional treatment (SRP).